2022
DOI: 10.3390/nu14224775
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary Fibers in the Management of IBD Symptoms

Abstract: Inflammatory bowel diseases (IBDs) are chronic, progressive, immune-mediated diseases of the intestinal tract. The main subtypes of IBDs are Chron’s disease (CD) and ulcerative colitis (UC). The etiology is still unclear, but there are genetic, environmental and host-related factors that contribute to the development of these diseases. Recent literature has shown that dietary therapy is the cornerstone of IBD treatment in terms of management of symptoms, relapse and care of the pathology. IBD patients show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 132 publications
0
5
0
2
Order By: Relevance
“…Therefore, increasing dietary fiber intake is necessary to help maintain intestinal health. Furthermore, dietary fiber has been found to provide other health advantages, such as lowering the risk of chronic illnesses such as diabetes, heart disease, and some cancers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing dietary fiber intake is necessary to help maintain intestinal health. Furthermore, dietary fiber has been found to provide other health advantages, such as lowering the risk of chronic illnesses such as diabetes, heart disease, and some cancers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, our growing comprehension of the significance of fiber for gastrointestinal health has highlighted the importance of IBD patients achieving an adequate dietary intake as well [ 4 , 47 ]. Although research studies on the role of fiber in the prevention and treatment of IBD in humans are limited [ 48 ], existing intervention trials have shown that dietary fibers can improve IBD symptoms [ 49 ], enhance health-related quality of life [ 50 ], balance inflammation [ 47 ], modulate immune responses [ 51 ], and help mitigate dysbiosis by restoring the gut microbiome [ 52 ]. Dietary fibers mediate these beneficial effects though byproducts of dietary fermentation of MAC, principally SCFA [ 53 , 54 ], and also by preserving the mucus layer barrier by promoting mucus synthesis and secretion [ 16 , 55 ].…”
Section: Nutritional Recommendations In Ibd About Fiber Intakementioning
confidence: 99%
“…Also considering the lack of clinical evidence directly implicating SCFAs in the resolution of inflammation or mucosal healing [ 49 , 82 , 83 ], large-scale prospective, longitudinal studies with characterization of gut microbiota composition and functions and with evaluations of SFCA (final byproducts of fiber fermentation) are strongly required to link dietary fibers, the microbiome, and SFCA’s production to specific favorable outcomes and objective measures (especially the reduction of inflammation through fecal calprotectin or endoscopic assessment).…”
Section: Dietary Fiber In Ibd: What Are We Missing To Change the Para...mentioning
confidence: 99%
“…In most instances, diet changes to become one that is low in dietary fibre and meat. A diet that is rich in fibres has been shown to have a protective effect on IBD [13]. However, as countries become more industrialized and urbanized, the intake of a diet that is high in fibre tends to reduce.…”
Section: Ibd Prevalence and Incidencementioning
confidence: 99%